Pengaruh Latihan Pliometrik Terhadap Peningkatan Power Otot Tungkai Atlet Gulat - Swandika Pinem; Irfan Deny Oktavian; Muhammad Fitrah Mubarak; Fachrun Nisa Sofiyah Khasanah (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2026)
This study aims to determine the effect of plyometric training on increasing leg muscle power in wrestling athletes. The method used was a pre-experiment with a one-group pretest-posttest design, and involved 40 wrestling athletes selected through a purposive sampling technique. The test instrument used in this study was a standing broad jump, and the data were analyzed using normality and homogeneity tests as prerequisite tests, then continued with a paired t-test and calculating the average increase. The results showed that: (1) there was a significant increase in leg muscle power in wrestling athletes, namely 183.55 before treatment and increasing to 186.97 after participating in the plyometric training program; (2) the data in this study were normally distributed and homogeneous; (3) the significance value of the t-test was 0.000 < 0.05, which explains that there is a significant effect. The conclusion of this study is that there is a significant effect of plyometric training on increasing leg muscle power in wrestling athletes. Keywords: Leg Muscle Power, Plyometric Training, Wrestling